The doctrine of God in reformed orthodoxy, Karl Barth, and the Utrecht School a study in method and content - Velde, Roelf T. te. (Leiden ; Boston : Brill, 2013)
In The Doctrine of God Dolf te Velde examines the interaction of method and content in three historically important accounts of the doctrine of God.
Includes bibliographical references and index.
Description based upon print version of record.
Keywords: God (Christianity) -- History of doctrines -- 20th century; Reformed Church -- Doctrines; Barth, Karl, -- 1886-1968.; RELIGION / Christian Theology / General; Electronic books